2020
DOI: 10.30560/as.v1n1p39
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Time of Earthing Up on Yield and Yield Parameters of Irish Potato (Solanum Tuberosum L.) in Zaka District, Zimbabwe

Abstract: Potato (Solanum tuberosum L) is a strategic national food security crop in that can be used as a supplement for carbohydrates. It is the fastest growing staple food crop and source of income for poor smallholder farmers. There is limited documentation on effects of earthing up irish potatoes on yield and yield components in Zimbabwe. A field experiment was conducted in Zaka district of Masvingo province in Zimbabwe during the 2018/19 cropping season. The aim of the study was to investigate the effect of time o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 0 publications
1
6
0
Order By: Relevance
“…Ethiopia who reported increased tuber yields with the use of cattle manure and mineral fertiliser on potatoes. Results from this project were in support of results bySakadzo et al (2020) who reported increased tuber yields with the use of earthing up potatoes in Zimbabwe (Zaka district). Results from this experiment corroborate with report by Masvodza…”
supporting
confidence: 86%
See 3 more Smart Citations
“…Ethiopia who reported increased tuber yields with the use of cattle manure and mineral fertiliser on potatoes. Results from this project were in support of results bySakadzo et al (2020) who reported increased tuber yields with the use of earthing up potatoes in Zimbabwe (Zaka district). Results from this experiment corroborate with report by Masvodza…”
supporting
confidence: 86%
“…Lack of knowledge about earthing up of potatoes (Sakadzo et al, 2020) and inadequate use of mineral and organic fertiliser has contributed to low potato yields in smallholder farming systems (Masvodza, 2015). There is need for proper dissemination information about these technologies to smallholder farmers as means of improving potato tuber yields.…”
Section: Research Articlementioning
confidence: 99%
See 2 more Smart Citations
“…[18] and [28] observed that earthing up of potato crop during the active plant growth period improved the soil condition which enabled proper root growth. They indicated that proper root growth enhanced efficient nutrient absorption which facilitated better growth and development consequently increasing fruit quality which can stay long in the post-harvest period.…”
Section: *Means Followed By the Same Letter(s) Along The Column For E...mentioning
confidence: 99%